The impact of Yb3+ concentration on multiband upconversion in a single NaYF4:Yb/Er microcrystal determined via nanosecond time-resolved spectroscopy. Issue 42 (7th October 2022) - Huang, Hanchang; Yuan, Maohui; Xing, Zhongyang; Cui, Wenda; Yu, Tongcheng; Hu, Shuai; Zhao, Guomin; Guo, Chuan; Han, Kai
Abstract : In lanthanide-sensitized upconversion (UC) nanomaterials, the typical sensitizer Yb 3+ can significantly modulate the codoped activator (such as Er 3+ ions) to generate multiband transitions. Abstract : In lanthanide-sensitized upconversion (UC) nanomaterials, the typical sensitizer Yb 3+ can significantly modulate the codoped activator (such as Er 3+ ions) to generate multiband transitions. However, the kinetics of these multiband emissions affected by the Yb 3+ concentration remains unclear. In this work, we employ nanosecond time-resolved spectroscopy to investigate a single optically trapped NaYF4 :Yb/Er microcrystal (MC) doped with different Yb 3+ concentrations. Interestingly, high doping Yb 3+ ions shorten the UC response time by a factor of 10 (from ∼1 μs to ∼100 ns) compared to low doping Yb 3+ . Meanwhile, 430 nm light ( 4 G7/2 → 4 I11/2 ) emitted before 654 nm ( 4 F9/2 → 4 I15/2 ) with Yb 3+ dramatically increasing (opposite to the normal low Yb 3+ doping cases), representing a new four-photon pathway ( 4 I15/2 → 4 I11/2 → 4 F7/2 → 2 H11/2 → 4 S3/2 → 2 G7/2 → 4 G11/2 → 2 H9/2 → 2 D5/2 → 4 G7/2 ). Furthermore, we observed a broad range of time-dependent emission color, changing from being initially green over near-white to red. Particularly, the red emission is dominated in the decay process, yielding insight into the fundamental multiband UC kinetics. The result shows that varying the Yb 3+ doping concentration provides a way to control the energy flow between the energy levels of Er 3+ ions, which can modulate the response time and color evolution of UC on Yb/Er doped materials. This can direct the prospective development of fast-response optoelectronic devices, photocatalysis, and UC displays in the future.